Przesłanki prawne innowacyjnych przekształceń jednostek ochrony zdrowia - Kachniarz, Marian (Legal Framework for Innovative Transformations of Health Care Units, 2008)
The article identifies basic legal dysfunctions in the activity of health care units. It makes a state diagnosis serving as restricting directions planning which effectively eliminate this system inefficiency. Because these actions have not had legal solutions creating full solutions, attempts of innovative methods using creatively existing legal formulas have appeared. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 61-67